Evidence for an intrinsic factor promoting landscape genetic divergence in Madagascan leaf-litter frogs - Wollenberg Valero, Katharina C. (Frontiers in Genetics, 2015)
The endemic Malagasy frog radiations are an ideal model system to study patterns and processes of speciation in amphibians. Large-scale diversity patterns of these frogs, together with other endemic animal radiations, led to the postulation of new and the application of known hypotheses of species diversification causing diversity patterns in this biodiversity hotspot. Both extrinsic and intrinsic factors have been studied in a comparative framework, with extrinsic factors usually being related to the physical environment (landscape, climate, river catchments, mountain chains), and intrinsic factors being clade-specific traits or constraints (reproduction, ecology, morphology, physiology). Despite some general patterns emerging from such large-scale comparative analyses, it became clear that the mechanism of diversification in Madagascar may vary among clades, and may be a multifactorial process. In this contribution, I test for intrinsic factors promoting population-level divergence within a clade of terrestrial, diurnal leaf-litter frogs (genus Gephyromantis) that has previously been shown to diversify according to extrinsic factors. Landscape genetic analyses of the microendemic species G. enki and its widely distributed, larger sister species G. boulengeri over a rugged landscape in the Ranomafana area shows that genetic variance of the smaller species cannot be explained by landscape resistance alone. Both topographic and riverine barriers are found to be important in generating this divergence. This case study yields additional evidence for the probable importance of body size in lineage diversification.